Ferroptosis and its role in skeletal muscle diseases - Wang, Ying; Zhang, Zepeng; Jiao, Weikai; Wang, Yanyan; Wang, Xiuge; Zhao, Yunyun; Fan, Xuechun; Tian, Lulu; Li, Xiangyan; Mi, Jia (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is characterized by the accumulation of iron and lipid peroxidation products, which regulates physiological and pathological processes in numerous organs and tissues. A growing body of research suggests that ferroptosis is a key causative factor in a variety of skeletal muscle diseases, including sarcopenia, rhabdomyolysis, rhabdomyosarcoma, and exhaustive exercise-induced fatigue. However, the relationship between ferroptosis and various skeletal muscle diseases has not been investigated systematically. This review’s objective is to provide a comprehensive summary of the mechanisms and signaling factors that regulate ferroptosis, including lipid peroxidation, iron/heme, amino acid metabolism, and autophagy. In addition, we tease out the role of ferroptosis in the progression of different skeletal muscle diseases and ferroptosis as a potential target for the treatment of multiple skeletal muscle diseases. This review can provide valuable reference for the research on the pathogenesis of skeletal muscle diseases, as well as for clinical prevention and treatment.